Pragmatic/Religious and Moral Values in Hermana HMT’s Drama Script “Robohnya Surau Kami” (“The Collapse of Our Mosque”) - Lusi Komala Sari; Bede Blaise Chukwunyere Onwuagboke (International Journal of Evaluation and Research in Education (IJERE), 2015)
Life in heaven is the hope of all religious human. Yet, to reach the paradise as promised to all faithful is not an easy road. It needs the balance of earthly life and hereafter’s life to reach the place which is promised by God. The drama Robohnya Surau Kami (RSK) created by dramatist Hermana HTM which is adapted from a short story written by A.A. Navis conveys the aforementioned. Using descriptive technique to analyze Drama RSK it is found that the drama script is created by structural elements as other literary works. The social-religious theme presented in flashback plot made this drama script to heave the readers’ imagination upward. The dialogue which made the gradation of character of each character in the drama brings out the uniqueness of Drama RSK. Unfortunately, the presentation of such an interesting script was poorly supported by various means of literary and dramatics that appear blurred. Despite this, the drama revealed pragmatic view which symbolizes real life situations full of religious and moral lessons for edifying religious and good social life in the society.